Neurogenic and non-neurogenic responses in the urinary bladder of hibernating hamster - Pinna, Christian (1998)
1. Purinergic and cholinergic components of parasympathetic neurotransmission and contractile responses to exogenous α,β-methylene ATP, acetylcholine, substance K, substance P, calcitonin gene-related peptide, vasoactive intestinal polypeptide and capsaicin have been investigated in the urinary bladder of hibernating hamsters (4 weeks), cold exposed (4 weeks) and age-matched controls. 2. Electrical field stimulation (EFS) evoked increased frequency-dependent contractions in the detrusor strips from hibernating hamsters compared with those obtained from cold-exposed and age-matched animals. Tetrodotoxin (10(−6) M) completely blocked the frequency-dependent contractions in all groups. 3. The purinergic component of the parasympathetic neurotransmission was not affected in hibernating and cold-exposed animals while the cholinergic component was increased with respect to age-matched animals. The neurogenic response to EFS, still present after incubation with atropine (10(−6) M) and suramin (10(−4) M), was attenuated by indomethacin (10(−6) M) and blocked by tetrodotoxin (10(−6) M). 4. Exogenous administration of α,β-methylene ATP elicited a significantly reduced contraction in strips from hibernating and cold-exposed hamsters relative to age-matched animals. The contractile response to exogenous acetylcholine was greater in the detrusors from hibernating hamsters than in cold-exposed and age-matched animals. Substance K elicited reduced contractions in preparations from hibernating animals compared with cold-exposed and control animals. Calcitonin gene-related peptide, vasoactive intestinal polypeptide, substance P and capsaicin did not elicit any relaxant or contractile response either at resting tone or in carbachol (5×10(−7) M)-precontracted tissues. 5. In summary, our findings indicate that 4 weeks of hibernation can significantly increase neurogenic responses in the hamster urinary bladder. This appears to be due to an increase in postjunctional responses to acetylcholine. In contrast, there was a decrease of the postjunctional responses to the parasympathetic cotransmitter ATP and also to the sensory-motor neurotransmitter substance K.